Recruitment of an Activated Gene to the Yeast Nuclear Pore Complex Requires Sumoylation - Saik, Natasha O.; Park, Nogi; Ptak, Christopher; Adames, Neil; Aitchison, John D.; Wozniak, Richard W. (Frontiers in Genetics, 2020)
In addition to their role in regulating transport across the nuclear envelope, increasing evidence suggests nuclear pore complexes (NPCs) function in regulating gene expression. For example, the induction of certain genes (e.g. yeast INO1) is accompanied by their movement from the nuclear interior to NPCs. As sumoylation has been linked to the regulation of chromatin spatial organization and transcriptional activity, we investigated the role of sumoylation in the expression and NPC recruitment of the INO1 gene. We observed that induction of INO1 is accompanied by increased sumoylation of proteins associated with specific regions along the INO1 locus. These sumoylation events are largely dependent on the SUMO E3 ligase Siz2/Nfi1. Furthermore, we show that Siz2-mediated sumoylation functions to target the INO1 locus to the NPC where it interacts with the SUMO isopeptidase Ulp1. Our data suggest that this interaction is required for both the association of INO1 with the NPC and for its normal expression. These results imply that sumoylation is a key regulator of INO1 targeting to the NPC, and a cycle of sumoylation and NPC-associated desumoylation events contribute to the regulation of INO1 expression.